Process optimization of vacuum-fried tinumbaga jackfruit (Artocarpus heterophyllus) bulbs chips - Dela Cruz, Raphael Alfonso L.; Villarino, Casiana Blanca J. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Jackfruit -- Philippines; Food industry and trade -- Philippines; Tinumbaga jackfruit